Professional Encounters in TESOL
XXVII, 262 p.
Keywords: An investigation of the developing discourses of English Language teachers in teaching and training. Showing how teachers are shaped by the discourses they participate in and how they shape these discourses. By analyzing professional development through professional discourse the book sheds light on what teachers do and why they do it.